PANEX – Pan Express - Reymundo Niño Neira, Carlos Alfonso (2022)
PANEX is a bread delivery app that seeks to satisfy the needs of its two target audiences thanks to its double value proposition: for users it is the “Netflix of bread” because it is bread by subscription. Thanks to our different plans, they can have fresh bread at home, just in time, on a scheduled basis and purchased from local bakeries. On the other hand, for bakeries, PANEX is "the Uber of Bread" because we amplify the connection with their consumers, innovating with technology and allowing them to increase their sales and have information on their consumers. In this sense, PANEX aims to transform the baking industry and promote a culture of fresh bread in every home in Peru, and its purpose is to connect local bakeries, with a constant and permanent demand from consumers (thanks to our plans), increasing and strengthening their community relationship through fresh bread. For the initial research, a non-experimental, cross-sectional, qualitative research was carried out, with the sample of about 140 people, between 30 and 60 years old from the San Borja district. After the development of the strategic, marketing, sales, operational, and financial plans, it is concluded that the project is highly viable, attractive for the chosen consumer segment, and can obtain very positive results.